Odpowiedzi

2010-03-04T15:26:40+01:00
A)2(x+3)=10
2x+6=10
2x=10-6/*2
x=2
b)3(x-1)+2=8
3x-3+2=8
3x=8-2+3/*3
x=3
c)2(13-x)-9=1
26-2x-9=1
-2x=1+9-26/*(-2)
x=8
d)3(1-x)+2=-7
3-3x+2=-7
-3x=-7-2-3/*(-3)
x=4
e)3(x+3)=2(x+4)+x+1
3x+9=2x+8+x+1
0=0
f)4(x-2)-2(x-4)=5(x+1)-36
4x-8-2x+8=5x+5-36
4x-2x-5x=5-36
-3x=-31/*(-3)
x=10 1/3
g)4(x-2)-2(x-4)=5(x+1)-3x
4x-8-2x+8=5x+5-3x
0=5 równanie sprzeczne
h)2(x-4)=2(2x-1)+6(x+1)
2010-03-04T15:31:11+01:00
A)2x+6=10
2x=4
x=2
b)3x-3+2=8
3x-1=8
3x=9
x=3
c)26-2x-9=1
-2x=-16
x=8
d)3-3x+2=-7
-3x+5=-7
-3x=-12
x=4
e)3x+9=2x+8+x+1
3x+9=3x+9
0=0
f)4x-8-2x+8=5x+5-36
2x=5x-31
-3x=31
x=-31/3=10 1/3
g)4x-8-2x+8=5x+5-3x
2x=2x+5
0=5 równanie sprzeczne
h)2x-8=4x-2+6x+6
2x-8=10x+4
-8x=12
x=-12/8=-3/2=-1 1/2


2010-03-04T15:35:16+01:00
A.
2x+6=10
2x=10-6|÷2
x=5

b.
3x-3+2=8
3x=8-2+3
3x=9|÷3
x=3

c.
26-2x-9=1
-2x=1+9-26
-2x=-16|÷(-2)
x=8

d.
3-3x+2=-7
-3x=-7-2-3
-3x=-12|÷(-3)
x=4

e.
3x+9=2x+8+x+1
3x-2x-x=8+1-9
0=0

f.
4x-8-2x+8=5x+5-36
4x-2x-5x=5-36+8-8
-3x=-31|÷(-3)
x=10 1/3

g.
4x-8-2x+8=5x+5-3x
4x-2x-5x+3x=5+8-8
0=5
r. sprzeczne

h.
2x-8=4x-2+6x+6
2x-4x-6x=-2+6+8
-8x=12|÷(-8)
x=-1,5